The Future of Research in Tourette Syndrome - Andrea E. Cavanna; Conor Kavanagh; Mary M. Robertson (Behavioural Neurology)
Tourette syndrome (TS) is a neurological condition first described by Georges Gilles de la Tourette in 1885. TS was largely thought of as a rare and bizarre condition until the 1960s, when the beneficial effects of neuroleptics on tic symptoms led to an exponential increase in neuroscientific research. Today TS is known to be a relatively common condition that is frequently misdiagnosed due to a combination of its variable manifestation and the waxing and waning of tic frequency and severity. Although there has been a paucity of research on TS compared to other movement disorders, in recent years TS has garnered increasing interest and has shown a number of novel and complex sides, about which much is yet to be learnt. The present article discusses where research has taken us thus far and where it is heading in all the major facets of this fascinating condition.